Investigating the Influence of Process Parameters of ZNC EDM on Machinability of A6061/10% SiC Composite - Balbir Singh; Jatinder Kumar; Sudhir Kumar (Advances in Materials Science and Engineering)
A6061/10% SiC composite has been fabricated by mechanical stir casting process. Fabricated composite has also been characterized through optical microscopy, X-ray diffraction analysis (XRD), scanning electron microscopy analysis (SEM) with energy dispersive X-ray techniques (EDX), and thermogravimetric/differential thermal analysis (TG/DTA). The composite has been experimentally investigated for its machinability using Z-axis numerically controlled (ZNC) electrodischarge machining (EDM) process. The effects of the four process parameters, namely, current, gap voltage, pulse-on time, and pulse-off time are investigated on material removal rate (MRR), tool wear rate (TWR), and surface roughness (SR) by varying one parameter at a time approach. Optical microscopy and SEM analysis revealed the uniform distribution of SiC particles in aluminum matrix phase. XRD investigation corroborated the elemental composition of 6061 Al alloy and reinforcement particles. Thermal analysis shows stability of composite upto 650°C. The machinability characteristics, namely, MRR, TWR, and SR have been interpreted using graphical representations. The study indicates that all the machining parameters affect the machining performance of A6061/10% SiC composite. Optimum machining performance has been realized at the lower setting of current and pulse-on time and the optimum setting of pulse-off time and gap voltage.